A Study of the Strategies Employed in the Rendering of Technical Language (Aarhus University, 2014)
The volume includes contributions on the cognitive processes underlying translation and interpreting, which represent innovative research with a methodological and empirical orientation. The methodological section offers an assessment/validation of different time lag measures; discusses the challenges of interpreting keystroke and eye-tracking data in translation, and triangulating disfluency analysis and eye-tracking data in sight translation research. The remainder of the volume features empirical studies on such topics as: metaphor comprehension; audience perception in subtitling research; translation and meta-linguistic awareness; effect of language-pair specific factors on interpreting quality. A special section is dedicated to expertise studies which look at the link between problem analysis and meta-knowledge in experienced translators; the effects of linguistic complexity on expert interpreting; strategic processing and tacit knowledge in professional interpreting.
Keywords: Biên phiên dịch,Translating and interpreting